THE SLEEP SOLUTION: EXAMINING THE IMPACT OF SLEEP EDUCATION-INTERACTION IN COMBATTING CHILDHOOD OBESITY – A SYSTEMATIC REVIEW - Ioannou, Maria; Antoniou, Sophia (Research Journal of Health, Medicine and Nursing, 2024)
Childhood obesity and sleep problems are two major public health issues. There is a growing body of evidence to suggest that these two problems are linked. Short sleep duration has been associated with an increased risk of childhood obesity. This is thought to be due to a number of factors, including hormonal changes that affect appetite regulation, increased calorie intake, and decreased physical activity. Sleep timing patterns may also play a role in childhood obesity risk. For example, children who go to bed late and wake up late are more likely to be obese than children who go to bed early and wake up early. The relationship between childhood obesity and sleep problems is complex and not fully understood. However, the evidence suggests that these two problems are interconnected and that addressing sleep problems may be an important strategy for preventing childhood obesity